The Impact of Financial literacy on Retirement Planning in Malaysia - Guzadhur, Pritika (2017)
Malaysia expects an expansion in its aging population in the near future. Retirement transition experiences will vary for each individual depending on their financial retirement planning initiation. Several studies have primarily focused on financial literacy. But, there appears to be a gap between the financial literacy level of individuals and its impact on retirement plan initiation and its subsequent impact on life satisfaction. This study focuses on the impact of financial literacy on retirement planning. Its main objectives are to assess the financial literacy level in Malaysia, identifying the different financial products used by Malaysians and examining financial learning. Moreover, it also aims to examine the impact of financial literacy on retirement plan initiation and life satisfaction. Finally, it compares the behaviour of males and females with regards to financial literacy and financial learning. The research method used is online surveys. A total of 202 valid responses were analysed. Results show that the financial literacy level of Malaysians is relatively average. It can be noted that Malaysians do start saving early but there is a high dependency on savings, cash deposits and money market funds. An increase in financial knowledge will enable them to make the most of all the financial products. This study concludes that an increase in financial literacy will allow for retirement planning. However, results also indicate that retirement planning initiation does not have any impact on life satisfaction.